Increased Cellular Uptake of ApoE3- or c(RGD)-Modified Liposomes for Glioblastoma Therapy Depending on the Target Cells - Larissa J. Lubitz; Moritz P. Haffner; Harden Rieger; Gero Leneweit (MDPI AG, 2024)
As effective treatment of glioblastoma is still an unmet need, targeted delivery systems for efficient treatment are of utmost interest. Therefore, in this paper, surface modifications with a small peptide c(RGD) or physiological protein (ApoE3) were investigated. Cellular uptake in murine endothelial cells (bEnd.3) and different glioma cells (human U-87 MG, rat F98) was tested to elucidate possible differences and to correlate the uptake to the receptor expression. Different liposomal formulations were measured at 1 and 3 h for three lipid incubation concentrations. We calculated the liposomal uptake saturation S and the saturation half-time t1/2. An up to 9.6-fold increased uptake for ApoE3-modified liposomes, primarily in tumor cells, was found. Contrarily, c(RGD) liposomes showed a stronger increase in uptake in endothelial cells (up to 40.5-fold). The uptake of modified liposomes revealed enormous differences in S and t1/2 when comparing different tumor cell lines. However, for ApoE3-modified liposomes, we proved comparable saturation values (~25,000) for F98 cells and U-87 MG cells despite a 6-fold lower expression of LRP1 in F98 cells and a 5-fold slower uptake rate. Our findings suggest that cellular uptake of surface-modified liposomes depends more on the target structure than the ligand type, with significant differences between cell types of different origins.